2012
DOI: 10.1039/c2md00253a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and overcoming aminoglycoside resistance caused by N-6′-acetyltransferase

Abstract: Aminoglycosides occupy a special niche amongst antibiotics in part because of their broad spectrum of action. Bacterial resistance is however menacing to render these drugs obsolete. A significant amount of work has been devoted to understand and overcome aminoglycoside resistance. This mini-review will discuss aminoglycoside-modifying enzymes (AMEs), with a special emphasis on the efforts to comprehend and block resistance caused by aminoglycoside 6′-N-acetyltransferase (AAC(6′)). Graphical AbstractResistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 123 publications
(181 reference statements)
0
31
0
1
Order By: Relevance
“…Following these developments, there was a period with relatively few additions to the field of aminoglycosides followed by another period characterized by new approaches that took advantage of the deeper understanding of different aspects of the biology and structure of aminoglycoside modifying enzymes as well as the advances in synthetic chemistry. As a consequence, numerous new generation aminoglycosides, also known as neoglycosides, started to be synthesized [ 19 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Of the several neoglycosides existing in the pipeline, plazomicin (ACHN-490) ( Figure 2 ), which has been granted Breakthrough Therapy designation by the FDA in May 2017, is the one closest to be approved for human use [ 59 , 60 , 61 , 62 ].…”
Section: A Brief History Of Aminoglycoside Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following these developments, there was a period with relatively few additions to the field of aminoglycosides followed by another period characterized by new approaches that took advantage of the deeper understanding of different aspects of the biology and structure of aminoglycoside modifying enzymes as well as the advances in synthetic chemistry. As a consequence, numerous new generation aminoglycosides, also known as neoglycosides, started to be synthesized [ 19 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Of the several neoglycosides existing in the pipeline, plazomicin (ACHN-490) ( Figure 2 ), which has been granted Breakthrough Therapy designation by the FDA in May 2017, is the one closest to be approved for human use [ 59 , 60 , 61 , 62 ].…”
Section: A Brief History Of Aminoglycoside Antibioticsmentioning
confidence: 99%
“…Numerous kinds of compounds with robust inhibitory activity of AAC(6′)-I enzymes have been described and are listed in various comprehensive reviews [ 26 , 49 , 54 , 253 ]. An inhibitor of AAC(6′)-Ib was first designed by an NMR-fragment based-approach [ 254 ].…”
Section: Amikacinmentioning
confidence: 99%
“…AG–AcCoA bisubstrate inhibitors of AAC(6′) were designed as potential drug candidates and for mechanistic studies (Figure 11A) [43]. NEA-AcCoA with linkers of varying length (1–5C) proved to be good inhibitors of A AC(6′)-Ii, A AC(6′)-Iy, and A AC(6′)-Ie/APH(2″)-Ia, with nanomolar to micromolar potencies [101].…”
Section: Ame Inhibitorsmentioning
confidence: 99%
“…SAR studies revealed that the adenosine is not essential, but potency drops dramatically if more than one phosphate is removed [105]. Crystal structures demonstrate several hydrogen bond donors positioned to interact with the negatively charged phosphates, supporting their importance in potent inhibitor binding [43]. Recently, another attempt to overcome poor cell membrane permeability includes the design of bisubstrate prodrugs consisting of only an AG with a pantetheine linker (Figure 11B) [106].…”
Section: Ame Inhibitorsmentioning
confidence: 99%
“…Although considerable efforts are dedicated to designing new aminoglycosides that can overcome existing mechanisms of resistance [4, 9], other alternatives to counter the action of aminoglycoside modifying enzymes are being researched. They include the utilization of inhibitors of gene expression such as antisense oligonucleotide analogs [10-12], inhibitors of the enzymatic activity like those developed to overcome β-lactamase-mediated resistance to β-lactams [5, 13-18], or metal ion inhibitors of the acetylation reaction, which most probably act by protective chelation of the substrate antibiotic [19-22]. However, in spite of the efforts directed at designing inhibitors of aminoglycoside modifying enzymes or their expression, none are in use in the clinics yet [reviewed in 4, 5].…”
Section: Introductionmentioning
confidence: 99%